Meaning Shift of Exclusive Religious Text in Abyan al-Hawāij by K.H. Ahmad Rifa’i - Maskhur, Maskhur; Shabir, Muslich; Syukur, Fatah; Muhtador, Moh. (ADDIN, 2022)
This article examines the shift in the meaning of religious texts that transform from exclusive to inclusive in the book Abyan al-Hawāij by K.H. Ahmad Rifa’i. This reinterpretation of the text is given that the conflicts that occurred between the Rifa’iyah group and non-Rifa’iyah residents were mostly caused by the Rifa’iyah group’s textual reading of religious texts that were exclusive. This article reviews exclusive religious texts by showing their historicity (historical function), meaning development (meaning function), and implicative function (implicative function) in order to show a more proportional new meaning. The approach used in this study is hermeneutics of Gracia, critical discourse analysis of Fairclough, and intertextual of Kristeva. The analysis is focused on looking back at the structure of the text (textual analysis), the discourse built by the author (discursive analysis), and the socio-cultural practices surrounding the text. Hermeneutically, the text is then seen in terms of its historical function, the function of developing its meaning, and the function of its implications within the framework of the cultural function of the text. The results of the research show that the exclusive religious text in Abyan al-Hawāij is an oppositional and confrontational text built by the author as a response to the Dutch colonial socio-cultural and political realities in the archipelago at that time. Therefore, reading these texts must also see the discourse of the text. These texts actually have many meanings (multi-vocality). In principle, these meanings are equally acceptable in line with their respective discourses. Reading the exclusive text in Abyan al-Hawāij in the current era of religious tolerance and harmony requires understanding the historicity of the text so as not to get stuck in an exclusive understanding of religion.